ANALISIS TINGKAT PENERIMAAN KOPI TAHLIL SEBAGAI KULINER KEARIFAN LOKAL : PERSPEKTIF GENERASI MILENIAL - Rahayu Prasetiani, Titi Rahayu Prasetiani; Ragil Sutrisno, Catur; Tsamara (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Tahlil coffee is a typical Pekalongan coffee made from coffee beans mixed with various spices. The millennial generation has a lifestyle of socializing while drinking coffee. This study aims to examine coffee tahlil as a local culinary, whether it can be accepted by the millennial generation amidst the many choices of various other types of coffee. The research was conducted using a survey approach, which involved the millennial generation as respondents. The technical analysis uses descriptive analytical techniques to explain the level of acceptance of tahlil coffee based on coffee quality attributes among the millennial generation. Coffee tahlil has been accepted by the millennial generation. Coffee tahlil products as a whole are close to good, with a score range of 4-1, the average product attribute has a score of 2.93. This product attribute score is above the average value of 2.5. The taste of spices in the tahlil coffee, the aroma and suitability of the size of the tahlil coffee have been well appreciated, with a score above 3. Whereas what needs attention is the thickness and variety of servings which are at the bottom score.